PENERAPAN KEGIATAN EKSTRAKURIKULER PRAMUKA DALAM PEMBENTUKAN KARAKTER SISWA DI MTS ALMAHFUDZ SAPURAN WONOSOBO - Muhamad Syaiful Amin; Maryono Maryono; Salis Irvan Fuadi (CV. Aksara Global, 2023)
This study aims to describe the formation of student character through scout activities at Mts Almahfudz Sapuran Wonosobo. This research was conducted using field research using a qualitative descriptive approach, namely a research process that produces descriptive data in the form of statements and the results of interviews, observations, and documentation obtained directly from the field or research area. The results of this study were found in the formation of the character of class VII and VIII students who used the honor code learning model, which is a measure or standard of behavior for members of the Scout movement. In scouting learning a student is trained to become someone who has a leadership spirit and is based on the formation of self-character. As a member of Scouting, the values of a code of ethics and code of honor must be understood and understood by all members of the Scout Movement, they are expected to take an oath of scouting (scout promise) and be willing to carry out scout law (scout law). The words on the promise or the guiding oath or the law of guiding tri satya and keeping the dasa dharma. Thus the authors can conclude that there is influence in scout education in the formation of the character of class VII and VIII students at Mts Almahfudz Sapuran Wonosobo.